1953
DOI: 10.1109/ee.1953.6438076
|View full text |Cite
|
Sign up to set email alerts
|

Using relays for unbalanced faults on generators

Abstract: MEMBER AIEE FRANK VON ROESGHLAUB MEMBER AIEEr-pHE REVISION OF THE STANDARD describing JL "Short-Circuit Requirements" for synchronous rotat ing machines is of considerable interest to the relay engi neer. The quantitative statement of current-time capa bility of the generator makes available a basis for co ordination of system and machine relaying on unbalanced faults. The permissible time duration of unbalanced faults is expressed as a variable based on /|/ being constant, where is the negative-sequence compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Extensive studies have shown that, in the majority of cases, the negative sequence current relay will properly coordinate with other system-relaying equipment [22,23].…”
Section: Protection Of Generators Against Negative Sequence Currentsmentioning
confidence: 99%
“…Extensive studies have shown that, in the majority of cases, the negative sequence current relay will properly coordinate with other system-relaying equipment [22,23].…”
Section: Protection Of Generators Against Negative Sequence Currentsmentioning
confidence: 99%